2013
DOI: 10.1590/s1984-70332013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of stem straightness and genetic correlations in Eucalyptus cladocalyx in the semi-arid region of Chile

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
5
17
1
1
Order By: Relevance
“…According to McDonald et al (2003), most Eyre Peninsula subpopulations are relatively small and fragmented due to clearance for agriculture, while the largest and most continuous populations occur in the southern Flinders Ranges, where they are largely present in conservation parks, which is consistent with the clustering analysis of the present study. Finally, the results showed a significant genetic differentiation among natural provenances consistent with previous studies of phenotypic variation in morphological traits CANÉ-RETAMALES et al, 2011;CONTRERAS-SOTO et al, 2011;VARGAS-REEVE et al, 2013) and chemical compounds in wood durability (BUSH et al, 2011). This information allows for the establishment of a positive relationship between genetic controls and morphometric traits that could be useful for breeding programs.…”
Section: Resultssupporting
confidence: 88%
“…According to McDonald et al (2003), most Eyre Peninsula subpopulations are relatively small and fragmented due to clearance for agriculture, while the largest and most continuous populations occur in the southern Flinders Ranges, where they are largely present in conservation parks, which is consistent with the clustering analysis of the present study. Finally, the results showed a significant genetic differentiation among natural provenances consistent with previous studies of phenotypic variation in morphological traits CANÉ-RETAMALES et al, 2011;CONTRERAS-SOTO et al, 2011;VARGAS-REEVE et al, 2013) and chemical compounds in wood durability (BUSH et al, 2011). This information allows for the establishment of a positive relationship between genetic controls and morphometric traits that could be useful for breeding programs.…”
Section: Resultssupporting
confidence: 88%
“…Notably, other studies have confirmed that some whole-regression methods could overestimate the heritability values [50], and therefore, these findings should be interpreted with caution. Overall, all target traits had pedigree-based heritability estimates from low to moderate (h 2 = 0.08-0.34), which are in accordance with the range usually expected for forest tree growth, flowering and stem quality related traits, including E. cladocalyx [28,29,[51][52][53][54].…”
Section: Heritability Estimatessupporting
confidence: 78%
“…WD was measured indirectly according to Valenzuela et al [28]. STR was measured in the first two-thirds of the total height of tree and was considered as ordinal variables with four levels [53], in which a value of 0 if the stem was strongly twisted, a value of 1 if the stem presents moderate levels of curvature, a value of 2 if the stem was slightly curved, and 3 if the stem was completely straight. The SLD was calculated as the ratio between HT (m) and DBH (m).…”
Section: Plant Materials and Phenotypic Evaluationmentioning
confidence: 99%
“…The significance of the variances of progenies (genetic) at the 1% probability level by the F test, for the four experiments, indicates the existence of genetic variability between the progenies of each type of pollination and allows for genetic gains through selection (Silveira et al, 2016). This significant effect, in particular the progenies from self-pollination, in which of the four experiments obtained greater percentage gains in three of them, may be related to the higher level of homozygosis, expressing with it greater divergence between the progenies, the one that allows the percentage of larger genetic gains (Vargas-Reeve et al, 2013).…”
Section: Continuaçãomentioning
confidence: 90%